ExtraOrdinary - Schwab, Victoria (Schwab, Victoria. Villains series, 2021)
Torn from the world of 'Vicious', where death is not the end, only the beginning of extraordinary powers... Three new "EO"s must grapple with their new abilities... and with those who would hunt them down!